Proving the correctness of data link layer protocol in FDDI networks - Er, Chuan Teck (2009)
This thesis is concerned with the application of formal methods for the specification and verification of data link layer protocol in FDDI networks. The formal specification language PROMELA is used to formalise the procedure rules and correctness requirements of the protocol. Automated protocol validation techniques are employed to evaluate the correctness of the safety and liveness properties of the data link layer.